Association of smoking with risk of multiple sclerosis: A population-based study - Ramagopalan, S; Lee, J; Yee, I; Guimond, C; Traboulsee, A; Ebers, G; Sadovnick, A (2013)
Genetic and environmental factors have important roles in multiple sclerosis (MS) susceptibility. Several studies have shown an association between smoking and MS risk. Here, in a population-based Canadian cohort, we investigate the relationship between personal and maternal smoking exposure and the risk of MS. Using the longitudinal Canadian database, 3,157 MS cases and 756 spouse controls were administered questionnaires on active and passive smoking history. Mothers of cases and controls were also asked about their smoking exposure during pregnancy. The MS cases were more likely to have smoked than spouse controls (odds ratio 1.32, 95 % confidence interval 1.10-1.60, p = 0.003). This association was driven by an excess of ever-smokers in male MS cases. No association was seen with maternal active or passive smoking exposure during pregnancy. Ever-smoking is associated with increased MS risk in males. Further work is needed to understand the mechanism underlying this association. © 2013 Springer-Verlag Berlin Heidelberg.